A composiç\~ao da desigualdade no Brasil: Conciliando o censo 2010 e os dados do imposto de renda - Marcelo Medeiros; Juliana Castro de Galv\~ao; Luísa Nazareno (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– We propose a methodology to conciliate the distributions of incomes of Census 2010 and of DIRPF 2010 (personal income tax reports). Applying this methodology, we decompose inequality by classes, regions and sex, race and age groups. We use annualized incomes and detailed educational information about university degrees obtained. Our results suggest that the underestimation of incomes in household surveys lead to an underestimation of the role of elites in Brazilian inequality. These elites contribute disproportionally to inequality and the correction resulting from conciliation increase even more this contribution.
Keywords: D31; 330; income inequality; social stratification; regional inequality; income tax